Uses, Dependency Model Remains Useful Framework. (June 2014) - Fleming, Kenneth
Telephone survey data show that print media dependency was significantly and positively associated with readership of the printed community newspaper, while online media dependency was significantly and positively associated with the use of the newspaper's website and the Internet.